MODULATION OF THE TECHNOLOGICAL FUNCTIONALITY OF COWPEA BEAN FLOUR (Vigna unguiculata) (Var. Chiclayo marron) BY PARTICLE SIZE CLASSIFICATION (Revista de Investigación Intercultural ASAMPITAKOYETE, 2025)
Cowpea flour (Vigna unguiculata) has high functional potential in food systems, although the effect of particle size on its properties has been little studied. This study evaluated the influence of particle size on the physicochemical and techno-functional properties of cowpea flour, specifically the Chiclayo Marron variety. Three fractions (60, 120, and 200 mesh) were obtained by milling and sieving. pH, titratable acidity, ash, and moisture content were determined, as well as water and oil absorption capacity, foaming capacity, emulsifying capacity, and swelling capacity. The tests were performed in triplicate and analyzed using ANOVA and Tukey's test (p < 0.05). Reducing the particle size decreased the fractionation yield but significantly increased water and oil absorption and foaming capacity. Emulsifying capacity showed a non-linear behavior, while swelling capacity was independent of particle size. These results confirm that particle size classification is an effective strategy for modulating the functionality of cowpea flour.
Keywords: Vigna unguiculata; granulometry; technological functionality; retention capacity; functional flour